Bicara wasiat & pengurusan harta pusaka menurut Islam / Norlida Othman - Othman, Norlida (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2021)
This program has been successfully conducted by FSKM KP and collaborated with MyANGKASA Amanah Berhad and Agrobank Bahau on Wednesday 7th October 2020 through Google Meet platform. More than 900 participants have filled up the survey of Keberkesanan Program & more than 1700 viewers on FB Live in FSKM official page. This program has been hosted by Puan Norul Fadhilah binti Ismail and the talk was delivered by Encik Ahmad Sahrul bin Mohamad from MyANGKASA Amanah Berhad.